The pope of Palm Beach - Dorsey, Tim (Dorsey, Tim. Serge Storms series., 2018)
"From Florida's king of mayhem Tim Dorsey -- "compulsively irreverent and shockingly funny" (Boston Globe) -- the latest madcap entry in his New York Times-bestselling Serge Storms series"--